10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
IntroductionAnemia and packed red blood cell (PRBC) transfusion are common in preterm infants, and feeding management during transfusion remains uncertain.ObjectiveTo characterize current opinions and enteral feeding practices surrounding PRBC transfusion among U.S. NICU providers.MethodsWe conducted a voluntary, anonymous 10-item REDCap survey distributed through AAP SONPM and TECaN listservs; responses were analyzed descriptively.ResultsAmong 432 respondents, most were neonatologists in level III or IV NICUs. More than half reported a transfusion-related feeding guideline, yet practices varied widely. Most withheld or restricted feeds, with variation in interruption timing, refeeding, glucose monitoring, and diuretic use. NEC and transfusion-related acute gut injury were the main reasons for restriction.ConclusionFindings highlight substantial practice variation and persistent uncertainty, not a preferred feeding approach. Prospective multicenter studies are needed to guide safe, evidence-based peri-transfusion feeding practices.